Operationalization of COVID-19 Rapid Diagnosis Using Xpert® Xpress SARS CoV-2 Assay in Resource-Limited Settings: Early Implementation Lessons From Uganda - Nsawotebba, Andrew; Ibanda, Ivan; Ssentalo Bagaya, Bernard; Nyombi, Abdunoor; Kagirita, Atek; Tugumisirize, Didas; Mujuni, Dennis; Majwala, Robert Kaos; Ocen, Francis; Kabugo, Joel; Adam, Isa; Wekiya, Enock; et al. (Research Square, 2021)
The novel Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) that causes COVID-19 disease is a global challenge. Several countries have adopted testing, isolation, and tracing strategy towards the control of the COVID-19 pandemic, but access to rapid and accurate testing is still a global challenge. The conventional PCR – based assay is the most commonly used test yet it has huge costs, infrastructural, and procurement logistical challenges. The Xpert® Xpress SARS-CoV-2 test is an automated in – vitro diagnostic test for the qualitative detection of nucleic acid from SARS-CoV-2 within a turnaround time of 60 minutes on the widely used GeneXpert Dx Instrument Systems. Here we document the best practices and challenges encountered with the operationalization of Xpert® Xpress SARS-CoV-2 testing in a resource-limited setting. Materials and Methods: The Xpert® Xpress SARS-CoV-2 implementation followed an operational work plan that included; Laboratory COVID-19 policy and planning, situational analysis of the Laboratory network, country Xpert® Xpress SARS-CoV-2 assay verification, and rollout at Mutukula Port Health Laboratory. The Laboratory strategy was based on a set of six objectives; conducting infrastructural modifications, building a strong COVID-19 testing capacity, developing robust Laboratory Quality and Information Management Systems, establishing a Bio-risk management and Bio-banking capacity.
Keywords: COVID-19; Xpert® Xpress SARS CoV-2; Rapid diagnosis; Resource-Limited Settings; Implementation